2018
DOI: 10.1002/jbm4.10030
|View full text |Cite
|
Sign up to set email alerts
|

Age‐Related Deterioration of Bone Toughness Is Related to Diminishing Amount of Matrix Glycosaminoglycans (GAGs)

Abstract: Hydration status significantly affects the toughness of bone. In addition to the collagen phase, recent evidence shows that glycosaminoglycans (GAGs) of proteoglycans (PGs) in the extracellular matrix also play a pivotal role in regulating the tissue-level hydration status of bone, thereby affecting the tissue-level toughness of bone. In this study, we hypothesized that the amount of GAGs in bone matrix decreased with age and such changes would lead to reduction in bound water and subsequently result in a decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 76 publications
0
24
0
Order By: Relevance
“…With aging, changes in PG secretion and post-translational modifications influence their binding to collagen. In fact, the glycanation state of SLRPs can serve as a chronological age “footprint.” 5861 In mineralized matrix, the synthesis of Biglycan is reduced with age, and though the abundance of the PG form of Biglycan in bones appears to be stable throughout life, in articular cartilage and the intervertebral disc, there are noticeable changes: the GAG-free form of Biglycan is low in juveniles, but increases in adults until it becomes the predominant form. 62,63 For Decorin, though the GAG-free form is always a minor component, the level of glycosylated Decorin decreases with age, thereby slightly increasing the proportion of the GAG-free form.…”
Section: Slrp Expression and Localization During Development And Agingmentioning
confidence: 99%
“…With aging, changes in PG secretion and post-translational modifications influence their binding to collagen. In fact, the glycanation state of SLRPs can serve as a chronological age “footprint.” 5861 In mineralized matrix, the synthesis of Biglycan is reduced with age, and though the abundance of the PG form of Biglycan in bones appears to be stable throughout life, in articular cartilage and the intervertebral disc, there are noticeable changes: the GAG-free form of Biglycan is low in juveniles, but increases in adults until it becomes the predominant form. 62,63 For Decorin, though the GAG-free form is always a minor component, the level of glycosylated Decorin decreases with age, thereby slightly increasing the proportion of the GAG-free form.…”
Section: Slrp Expression and Localization During Development And Agingmentioning
confidence: 99%
“…The transmembrane domain allows for dimerization, whereas the cytoplasmic domain (composed of conserved regions C1 and C2 flanking a variable region [V]) interacts with kinases, the cytoskeleton and C1 mediates endocytosis 11,12 . GAGs, abundant in the extracellular matrix (ECM), are known to enhance bone regeneration and osteoblastogenesis by binding of the WNT inhibitor, sclerostin. However, with ageing the amount of GAGs, and in particular CS decreases in human cortical mineralised bone matrix, which has a detrimental effect on bone toughness and likely contributes to the agerelated deterioration of bone quality 13 . Previous research 14 has shown that HS GAGs are important in osteoblast differentiation and activity, and SDCs with attached GAGs, can modulate WNT signalling 15,16 , however SDC-WNT crosstalk in bone has not been clearly deciphered 4,17 and involvement of SDCs in bone physiology is poorly defined.…”
Section: One Of the Most Important Signalling Pathways Inducing Osteomentioning
confidence: 99%
“…Bone water content has recently attracted renewed interest as it has been shown to contribute to the overall toughness of bone, acting like a plasticizer 6265 . This indirectly emphasizes the importance of proteoglycans in the determination of bone strength 66 . Proteoglycans are non-collagenous components of the bone extracellular matrix and are characterized by the presence of one or more glycosaminoglycan polymers attached to a protein core 67 .…”
mentioning
confidence: 92%